Melatonin ameliorates liver fibrosis induced by bile-duct ligation in rats - (:unkn) unknown (CMA-CANADIAN MEDICAL ASSOC, 2010)
Background: Hepatic stellate cells, the main mediators in the pathogenesis of fibrosis, are triggered by free radicals and produce collagen. Melatonin is a powerful physiologic scavenger of hydroxyl radicals. It is also involved in the inhibitory regulation of the collagen content in tissue. There is no effective treatment available for liver fibrosis. Our objective was to evaluate the effects of melatonin on liver fibrosis induced by bile-duct ligation (BDL) in rats. Methods: We divided male Wistar rats (n = 32) into 4 groups. Two groups received BDL and 2 groups received sham operations. One of the BDL groups and one of the sham groups were administered melatonin (100 mg/kg/day via intraperitoneal injection), and the controls were given vehicle only. After 1 month, we biochemically evaluated the changes in hepatic fibrosis by measuring tissue collagen levels and histopathologic examination. We evaluated the levels of malondialdehyde (MDA), glutathione (GSH), luminal and lucigenin in tissue homogenates, and we studied proinflammatory cytokines in serum using commercially available kits. Results: Bile-duct ligation caused hepatic fibrotic changes, whereas melatonin suppressed these changes in 5 of 8 rats (p < 0.001). Bile-duct ligation resulted in increased collagen, MDA, luminal and lucigenin levels and decreased GSH levels, whereas melatonin reversed these effects. Conclusion: We found that melatonin functions as an effective fibrosuppressant and antioxidant, and the results suggest that it can be used as a therapeutic option.
Keywords: BILIARY-OBSTRUCTED RATS; HEPATIC-FIBROSIS; CARBON-TETRACHLORIDE; COLLAGEN CONTENT; REACTIVE OXYGEN; ACID; PINEALECTOMY; INHIBITION